THE INFLUENCE OF CELEBRITY ENDORSEMENT AND ELECTRONIC WORD OF MOUTH WITH BRAND IMAGE AS INTERVENING VARIABLE ON CONSUMERS’ PURCHASE INTENTION OF AZARINE SUNSCREEN IN SEMARANG - Shabrina Hulwani; Sudharto P Hadi; Andi Wijayanto (Universitas Diponegoro, 2025)
Azarine Cosmetic, a local brand, produces sunscreen and utilizes celebrity endorsements and electronic word of mouth (E-WOM), particularly online consumer reviews, as marketing strategy to increase product sales, create a favorable brand image, and attract consumer purchase intention. However, in 2023, Azarine’s sunscreen sales in Semarang outlets experienced fluctuations. Without effective marketing tactics, Azarine will risks losing its share in the competitive skincare market. This research aims to know the influence of celebrity endorsement and E-WOM through brand image as intervening variable on consumers’ purchase intention of Azarine suncreen in Semarang, tested based on variables but explained through the influence of each dimension/indicator on each variable. The total sample in this research are 100 people in Semarang with unidentified population, with the technique of non-probability sampling of purposive sampling type. Data was collected through questionnaires, literature reviews, and interviews. This explanatory research follows a quantitative approach and is processed using SPSS version 26. The result show that celebrity endorsement and E-WOM has positive influence on purchase intention, both directly and indirectly through brand image. Recommendations for Azarine include encouraging celebrities to provide authentic testimonials, reallocating budget to micro-influencers and customer-generated content, fostering positive E-WOM, and reformulating product ingredients.